Association between Myopia and Glaucoma in the United States Population - Qiu, Mary; Wang, Sophia Y.; Singh, Kuldev; Lin, Shan C. (Investigative ophthalmology & visual science, 2013)
To investigate the association between myopia and the prevalence of glaucoma. This cross-sectional study included 5277 participants from the 2005 to 2008 National Health and Nutrition Examination Survey, greater than or equal to 40 years old, without history of cataract or refractive surgery, who underwent auto-refraction measurement. The predictor was refractive status; emmetropia (-0.99 to +0.99 diopters [D]), mild myopia (-1.00 to -2.99 D), moderate myopia (-3.00 to -5.99 D), severe myopia (> -6.00 D), and hyperopia (> 1.00 D). The outcomes were self-reported glaucoma, vertical cup-to-disc ratio and visual field defects as found on frequency doubling technology (FDT) testing Odds of self-reported glaucoma were not significantly increased in mild (odds ratio [OR] 0.90, confidence interval [CI] 0.56-1.45), moderate (OR 1.40, CI 0.62-3.16), or severe (OR 0.26, CI 0.08-0.80) myopes compared with emmetropes. Odds of vertical cup-to-disc ratio greater than or equal to 0.7 were not significantly increased in mild (OR 0.84, CI 0.31-2.25), moderate (OR 0.37, CI 0.04-3.57), or severe (OR 0.85, CI 0.09-8.42) myopes compared with emmetropes. Odds of any visual field defects were significantly increased in mild (OR 2.02, CI 1.28-3.19), moderate (OR 3.09, CI 1.42-6.72), and severe (OR 14.43, CI 5.13-40.61) myopes compared with emmetropes. The χ(2) test indicated a significant difference (P = 0.001) in the distribution of subjects with each category of visual field status across subjects with each refractive status; the proportion of subjects with worse visual field defects increased with worsening myopia severity. The association between myopia and visual field defects may represent an increased risk of glaucoma among myopes, and the lack of association with self-reported glaucoma may suggest a need for greater glaucoma surveillance in this population.